(untitled) (St. Louis, Mo., 2007)
This full-color reference offers practical, evidence-based guidance on using more than 120 medicinal plants, including how to formulate herbal remedies to treat common disease conditions. A body-systems based review explores herbal medicine in context, offering information on toxicology, drug interactions, quality control, and other key topics. More than 120 herbal monographs provide quick access to information on the historical use of the herb in humans and animals, supporting studies, and dosing information. Includes special dosing, pharmacokinetics, and regulatory considerations when using herbs for horses and farm animals
Keywords: Veterinary Medicine,Thuốc thú y; Methods